Kinetic and Viscoelastic Study of Liquid Thermoplastic Matrix Based on Methyl Methacrylate Copolymers - Silveira, Daniel Consoli [UNESP]; da Silva Braga, Tiago Teixeira [UNESP]; dos Santos Conejo, Luiza [UNESP]; Junior, Antônio Carlos Ancelotti; Costa, Michelle Leali [UNESP]; Botelho, Edson Cocchieri [UNESP] (FapUNIFESP (SciELO), 2023)
The industries that have polymers as an important raw material in their production, such as the construction, automotive, electrical and electronic sectors, always seek innovations to cut costs, reduce weight, easiness of processing, maximizing mechanical properties, and recyclability. In this context, this work presents the study of the kinetic parameters and viscoelastic behavior of a new thermoplastic system initially liquid. Through differential scanning calorimetry (DSC) analysis, Brookfield viscosimetry; dynamic-mechanical analysis (DMA) and mathematical modeling with consolidated and standardized methods, it was possible to evaluate the polymerization kinetics and viscoelastic behavior of the material in solutions with different concentrations. The generated equations allow the prediction of the kinetic and gelation behavior of the material reducing the need for laboratory tests to determine polymer properties. The found results showed that concentrations of benzoyl peroxide initiator with 1wt% in the methyl methacrylate (MMA) copolymer solution have the best viscoelastic and dynamic-mechanical properties with a less expensive polymerization cycle.
Keywords: kinetic parameters; poly(methyl methacrylate); polymeric matrix; polymerization; thermoplastics; viscoelastic behavior